Characterization of a mobilizable megaplasmid carrying multiple resistance genes from a clinical isolate of Pseudomonas aeruginosa - Mei, Li; Song, Yang; Liu, Dongxin; Li, Yixiao; Liu, Li; Yu, Keyi; Jiang, Mengnan; Wang, Duochun; Wei, Qiang (Frontiers in Microbiology, 2023)
The horizontal transfer of antibiotic resistance genes mediated by plasmids has attracted widespread attention and seriously affects the effectiveness of modern medical treatment. In the current study, we isolated a multidrug-resistant Pseudomonas aeruginosa strain termed BJ86 from a patient's sputum specimen.Further sequencing analysis indicates that BJ86 carries an amazing 522.5kb-length megaplasmid pBJ86, which contained a 93.5kb-length multiple resistance region (MRR); 18 kinds of genes were identified as antibiotic resistance genes (ARGs) in this region, including tmexCD-oprJ, blaDIM-1, qnrVC6 that mediate multiple antibiotics resistance and the operons mer that mediates heavy metal mercury resistance. The co-selection mechanism of ARGs and heavy metal resistance genes (MRGs) on mobile elements may further exacerbate the horizontal transfer of resistance genes. In addition, there is also an 80kb variable region (VR) on the plasmid pBJ86, and the genes encoding relaxase and type IV coupling protein (T4CP) were determined in this region, both of which are related to the conjugation and transfer ability of the plasmid. Bioinformatics analysis shows that many functional genes have insertion sequences and transposases on their flanks, which may have been accumulated in the plasmid pBJ86 after multiple acquisition events. Conjugated transfer and in vitro tests for antimicrobial susceptibility verified the mobility and plasmid pBJ86-mediated resistance. To our knowledge, we firstly reported a mobilizable plasmid, which simultaneously carried tmexCD-oprJ, blaDIM-1, qnrVC6, and the operons mer as well as can be transferred with frequencies of 6.24×10 -7 transconjugants per donor cell.